‘TUNE IN/JOIN US': Mobilising Liveness as a Promotional Strategy in Film Trailer Exhibition - Stenson, Robert (2021)
This thesis investigates the ways in which ‘liveness’ has been mobilised by the US film industry during the exhibition of film trailers on broadcast television and online. It offers a lens to understand how Hollywood is not only responding to viewers’ increased ability to evade television advertising, but also to an online landscape where users’ attention is becoming increasingly difficult to attract and retain. In this emerging ‘new screen ecology’, we are witnessing how the established media organisations and practices of the twentieth-century are being challenged and reconfigured by a variety of digital technologies and online platforms.